Pengaruh Variasi Formulasi Campuran Daun Kelor dan Serai Dapur Terhadap Mutu Kombucha (Mocy) - Tedi Tedi; Zaenal Abidin; Edi Junaedi (Mahesa Research Center, 2023)
The abundant moringa and lemongrass plants can be used to make Kombucha products. By utilizing Moringa leaves and lemongrass which are fermented by Symbiotic Culture of Bacteria and Yeast (SCOBY) to become Kombucha. This study aims to determine the effect of variations in the formulation of a mixture of Moringa leaves and lemongrass on the chemical characteristic quality of Total Titrated Acid (TAT), presence of flavonoids, and organoleptic quality. This research is a quantitative research. The results of the study were the TAT value of formulation 1 (0.454%), formulation 2 (0.432%), formulation 3 (0.445%), and control (0.54%). The results of the analysis showed that variations in the formulation of a mixture of moringa leaves and lemon grass had no significant effect on the TAT value of Kombucha with F Count (0.93) F Table 5% (3.10). Flavonoids in Kombucha were tested qualitatively by 3 reagents seen from the color change. At 10% NaOH it showed a yellow brown color, 1% AlCl3 reagent was yellow, and H2SO4 reagent was pale yellow to yellow brown, and all samples showed positive results for the presence of flavonoids. Organoleptic assessment with color results X²r count (6.03) X²r table 1% (6.250), aroma X²r count (11.47) X²r table 5% (7.810), taste X²r count (18.91) X²r table 5 % (7,810). So that the variation in formulation has a significant effect on aroma and taste, but not on the color of Kombucha moringa leaves and lemon grass.